Math, asked by vibhanshu8441, 1 year ago

find the following products answer with photos ​

Attachments:

Answers

Answered by Anonymous
37

HeRe Is Your Ans

*******

 =  > (1 - m)(1 + m +  {m}^{2} ) \\  \\  =  > 1 + m +  {m}^{2}  - m -  {m}^{2}  -  {m}^{3}  \\  \\  =  >  -  {m}^{3}  + 1

 \fbox{ans =  -  {m}^{3} + 1 }

*****

 <marquee > hope it helps u

Answered by coolest27
4

Step-by-step explanation:

M power 3 + 1

I hope it will help you yaar

Have a great day and take care stay safe yaar ❤️❤️❤️

Similar questions